Analisis Pelaksanaan Supervisi Klinis dalam Meningkatkan Kualitas Pembelajaran di MI KH. Hasyim As’ari - Nurmala Sukmawati; Shobihatul Fitroh Noviyanti; Mas'udatun Nashicha; Hima Rosa Damayanti (Al-Kindi, 2026)
Improving the quality of learning in Madrasah Ibtidaiyah (MI) still faces various challenges, particularly teachers' limited ability to independently develop pedagogical competence and the high administrative burden on school principals. This study aims to analyze the implementation of clinical supervision in improving learning quality at MI KH Hasyim Asy'ari, covering supervision practices, approaches, functions, obstacles, and effectiveness evaluation. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with the principal and teachers, direct observation of supervision activities, and documentation study of supervision instruments and records. The results show that clinical supervision at MI KH Hasyim Asy'ari is conducted on a scheduled basis through three stages: pre-observation, classroom observation, and post-observation with direct and personal feedback. Clinical supervision has proven effective in improving teachers' pedagogical, professional, and social competencies. However, inconsistencies in follow-up actions were found, along with a generational gap between senior teachers and Gen Z teachers that creates communication barriers in the supervision process. In conclusion, clinical supervision implemented in a planned, humanistic, and sustainable manner is effective in improving learning quality at the madrasah, although more adaptive cross-generational communication strategies are needed to ensure equitable supervision for all teachers.